Factores condicionantes que influyen en el cumplimiento del programa de vacunación en menores de 5 años en el Centro de Salud El Cóndor Guasmo Sur. Diciembre 2022 - mayo 2023. - Gavilanes Monar, Geovanna Elizabeth (2023)
Worldwide, vaccines are known to be the most successful interventions for improving health outcomes. High vaccination coverage directly protects vaccinated individuals and indirectly exerts protective effects by delaying the transmission of vaccine-preventable diseases in the general population. Therefore, the aim of this research is to determine the conditioning factors that influence compliance with the vaccination program in children under 5 years of age at the "El Condor" health center, Guasmo Sur, in the period from December 2022 to May 2023. The research will be based on a mixed quantitative-qualitative methodological approach and will be an applied, field, exploratory-descriptive and cross-sectional research. As a result, it was obtained that more than half (54%) do not know how vaccines work, 33% did know the real effect of vaccines and 13% believed that the vaccine produced a vitamin effect in humans.